Healthcare professionals’ understanding and awareness of patient safety and quality of care in Africa: A survey study - Ente, Christopher; Oyewumi, Ajibike; Mpora, Odongkara Beatrice (International Journal of Risk & Safety in Medicine, 2010)
In Africa there is currently not a wide knowledge of patient safety and healthcare quality. There is inadequate data to measure the scale of medical error and its impact on the healthcare.We investigated the frontline staff experience, their awareness of medical error and willingness to participate in patient safety initiatives. This is a qualitative survey involving 60 healthcare professionals in 2 private and 2 public hospitals in Nigeria and Uganda. Findings highlighted that frontline staff have a good knowledge and understanding of medical error. Thirty percent of the participants said errors occur frequently while only 3.3% were not sure of how often errors occur in their hospitals. Inadequate research on patient safety in literature at present does not mean that medical errors or other issues that undermine patient safety do not occur in Africa. Factors that cause medical errors and the impact of such errors are known to healthcare professionals. They are willing to participate in healthcare improvement programmes. Our findings show the relevance of patient safety in the region and provide a focus for further work that would ultimately contribute to the identification of appropriate interventions that could improve patient safety in Africa.
Keywords: Patient safety; Medical error; Africa; Healthcare professionals